A systematic race course analysis and description of men's race performance in the Paralympic alpine skiing world cup slalom and giant slalom races of the 2014-2015 and 2015-2016 seasons - Bruhin, B.; Senn, I.; Flury, S.; Wolfsperger, F.; Boffi, G.; Lorenzetti, S. (Science and Skiing VII, 2018)
This study has given a broad overview of the Paralympic alpine skiing slopes and course settings and has shown that slope and course setting conditions vary in Paralympic alpine skiing World Cup GS and SL races. Additionally, this study has demonstrated significant differences between the mean performances of SCs within one season in the men`s standing and men`s sitting categories for the first time. As many other factors influence the performance of the athletes, interpretations must be made carefully. However, the results demonstrate the challenge of organizing completely fair conditions in Paralympic alpine skiing and the complexity of developing an appropriate classification system - a common problem in Paralympic sports. A possible limitation of this study is the low degree of variation in the slopes. Therefore, further data collection over several seasons is necessary.